Exploring the divergence in perspectives on clinical trial operations in South Korea during the COVID-19 pandemic: a comparison of a trial site and sponsors - Kim, Young-Sang; Kim, Anhye; Lee, Yil-Seob (Frontiers in Medicine, 2024)
During the COVID-19 pandemic, novel clinical trial methods known as decentralized clinical trials (DCTs) were rapidly introduced. The attitude toward operating clinical trials and perspectives on DCTs may differ between clinical trial sites and sponsors. The impact of the COVID-19 pandemic on clinical trials was investigated for a society of sponsors and a trial site in South Korea. The current difficulties and future perspectives on clinical trials were assessed and compared between the site and sponsors. Both the site and sponsors reported on their experiences with the challenges of conducting clinical trials during the pandemic era. While 64% of personnel from the site judged that the difficulties were solved by their own solutions, 67.6% of personnel from sponsors considered cooperation with trial sites as a key solution to overcome the difficulties. While half of the personnel from the site were skeptical of the changes in trial operation methods, the sponsors expected the institutionalization of DCT elements. In conclusion, with varying attitudes, sponsors and sites attempted to overcome the challenges of conducting clinical trials during the pandemic era. To conduct clinical trials effectively, both sponsors and sites must work closely together to find solutions with efficient communication. For the successful implementation of new tools such as DCTs, the government needs to solicit support from sponsors and sites and change regulations.